Body Language and Its Universal Meaning: the Interpretation of Body Language in the Little Black Book Film - Lalu Suhirman (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to examine body language, namely facial expressions that appear in film scenes entitled 'Little Black Book'. Therefore, this study discusses two research questions: 1) what conventional meaning is expressed by the facial expressions of central figures in 'Little Black Book' film? 2) what are the forms and patterns of body language that carry important messages besides facial expressions in 'Little Black Book' film? This study uses a qualitative approach to analyze data. The data source of this research is the film "Little Black Book". The data of this study are certain scenes related to body language. Data is collected through observation, which is watching carefully and repeatedly, and cutting or copying images that show gesture or gesture of body language. The result found was facial expressions which specified at upper neck, namely: head, eyes, and mouth. while the other parts of body language were hands and other acts of body language.